A study of flow in alluvial channels: the effect of large concentrations of fine sediment on the mechanics of flow in a small flume - Haushild, W. L., author; Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; United States Geological Survey, Colorado State University, publisher (Colorado State University. Libraries, 1960)
A flume study was made using a natural river sand as the bed material, median diameter = 0.54 millimeters. Clear-water flow was compared with flow containing from 6,000 to 65,000 parts per million of fine sediment (bentonite). The study shows that the form of bed roughness could be changed by adding sufficient fine sediment (bentonite) to the clear-water flow. The total bed material transport was decreased by 50 percent with increasing fine sediment concentration with the dune bed form and was increased by as much as 550 percent for the transition, standing wave, and anti-tune forms of bed roughness. Resistance to flow was less (C/√g increased by 45 percent) with fine sediment-laden flow than with clear-water flow for the dune, and transition bed forms; and was greater (C/√g reduced by 25 percent) for the standing waves and the anti-dunes. A narrow range of bentonite concentration for each form of bed roughness was established as a limit below which only minor changes in bed form, bed material transport, and resistance to flow occurred. The variation of the liquid proper ties, specific weight and viscosity, for water-bentonite dispersions were studied and their effect on the properties of the bed material particles measured. The fall velocity of the particles in a dispersion of 100,000 parts per million fine sediment in water was reduced to about one-half their fall velocity in clear water.
CER60DBS44.
A small flume study of the variance in resistance to flow, form of bed roughness, and total bed material transport caused by introducing large fine sediment concentrations into the flow over a sand bed.
Keywords: Stream measurements -- Mathematical models; Fluid dynamics -- Mathematical models